2019
DOI: 10.1001/jamaoto.2019.0269
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ibuprofen vs Acetaminophen and Severe Bleeding Risk After Pediatric Tonsillectomy

Abstract: IMPORTANCEIbuprofen is an effective analgesic after tonsillectomy alone or tonsillectomy with adenoidectomy, but concerns remain about whether it increases postoperative hemorrhage.OBJECTIVE To investigate the effect of ibuprofen compared with acetaminophen on posttonsillectomy bleeding (PTB) requiring surgical intervention in children. DESIGN, SETTING, AND PARTICIPANTSA multicenter, randomized, double-blind noninferiority trial was conducted at 4 tertiary medical centers (Massachusetts Eye and Ear Infirmary,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 26 publications
1
33
0
1
Order By: Relevance
“…8 Additionally, Dierks et al suggested in a noninferiority randomized clinical trial (RCT) that increased bleeding risk associated with Ibuprofen use could not be ruled out and that further investigation with regard to the dosing of Ibuprofen should be carried out for postoperative analgesia. 9 In contrast to this literature, Baugh et al suggested in the American Academy of Otolaryngology—Head and Neck Surgery tonsillectomy guidelines that NSAID pain relievers are safe and that they should be promoted for postoperative analgesia. 10 These claims were affirmed by Hartnick’s findings, which suggest that when 10 mg/kg doses of Ibuprofen given every 6 hours is compared with 15 mg/kg doses of Acetaminophen given every 6 hours there is no significant difference in bleeding rate when either is prescribed for post-tonsillectomy analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, Dierks et al suggested in a noninferiority randomized clinical trial (RCT) that increased bleeding risk associated with Ibuprofen use could not be ruled out and that further investigation with regard to the dosing of Ibuprofen should be carried out for postoperative analgesia. 9 In contrast to this literature, Baugh et al suggested in the American Academy of Otolaryngology—Head and Neck Surgery tonsillectomy guidelines that NSAID pain relievers are safe and that they should be promoted for postoperative analgesia. 10 These claims were affirmed by Hartnick’s findings, which suggest that when 10 mg/kg doses of Ibuprofen given every 6 hours is compared with 15 mg/kg doses of Acetaminophen given every 6 hours there is no significant difference in bleeding rate when either is prescribed for post-tonsillectomy analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…20 Other analyses that had a higher risk of bias because of observational study design identified a small but statistically significant increase in bleeding (OR, 1.38; CI, 1.11-1.72). 21 More recently, Diercks et al 22 completed a multicenter randomized controlled trial of 741 children undergoing tonsillectomy and/or adenotonsillectomy that randomized children to either ibuprofen 10 mg/kg or acetaminophen 15 mg/kg, with a primary outcome of rate of post-tonsillectomy bleeding requiring a return to the operating room. The authors found a rate of postoperative bleeding requiring a return to the operating room of 1.2% in the acetaminophen group and 2.9% in the ibuprofen group ( P = 0.12), but all patients in the study took ibuprofen every 6 hours for 9 days, which is far in excess of what is commonly used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, there is newer evidence in the literature that ibuprofen can increase risk of post-tonsillectomy hemorrhage in certain patient populations. [34][35] There is ongoing concern regarding increased postoperative hemorrhage when ketorolac is used for analgesia, but there is conflicting evidence regarding the safety of ketorolac in pediatric tonsillectomy. [36][37] The anesthesiologists who do use opioids in the PACU for a normal-weight child with severe OSA are most likely to use fentanyl (51.8%) which has a rapid onset and short duration of action.…”
Section: Discussionmentioning
confidence: 99%